Leaf traits of sal (Shorea robusta Gaertn.) populations selected from different regions of Bangladesh (Dhaka University Journal of Biological Sciences, 2021)
This study investigated the variation in leaf traits of Sal (Shorea robusta Gaertn.) by collecting leaf samples from the natural populations of Sal distributed in Madhupur National Park, Cumilla and Dinajpur areas of Bangladesh. Soil samples were collected at 0 - 10 cm depth near the base of the tree trunk of the respective plants selected for the collection of leaf samples. Soils were analyzed for moisture content, pH, electrical conductivity, available N, total P, and organic C contents. Data showed a range of variation in the responses of leaf traits of the three populations. However, none of the morphological and physiological traits showed significant differences except chlorophyll content (p = 0.0047). Conversely, significant difference appeared in most of the leaf anatomical properties such as stomatal pore index (p = 0.0369), open-close behavior (p = < 0.0001) and stomatal density (p = 0.0008) among the three forests. Stomatal density, pore index, and percent open stomata were higher in the Madhupur forest, while closed stomata were significantly higher in the Dinajpur forest. Thus, the present study indicated that although all leaf traits did not show a similar trend of response, leaf stomata were more responsive to different geographical distribution, which could be attributed to the variation in soil moisture conditions.Dhaka Univ. J. Biol. Sci. 30(2): 317-324, 2021 (July)